THE ECONOMICS OF VIOLATION BEHAVIOUR OF FISHERS IN INDONESIA, MALAYSIA AND THE PHILLIPPINES*) - Indah Susilowati (JOURNAL OF COASTAL DEVELOPMENT, 1999)
This paper examines the behavior of the fishers violating a zoning regulation under a condition of limited enforcement in the fisheries of Indonesia, Malaysia, and the Philippines. Rational utility theory is used as a framework for explaining compliance behavior. Samples of 304 violators from the study area were used in the analysis. Tobit model is employed in the analysis. The results indicate that economic, morality and social influence factors determine the overall violation decision of individual violators fishing in the prohibited area. In the general the findings of the study were consistent with the theoretical model of compliance behavior tested by previous researchers. Enforcement is costly thus to improve fishers’ compliance in the study area there is a need to used other determinants of compliance as such as morality and social influence factors. Fisheries management authorities should also explore alternative approaches for managing fisheries such as participatory or community-based management approaches. Such approaches may incur lower monitoring and enforcement costs. rateB R JEER. The best absolute growth (292,05g), daily growth rate (1,34%/day), FCR (2,31), PER (1,68) and NPU (8,37), were achieved by treatment B, followed by C and A. meanwhile, the best SR was achieved by treatment C and followed A, and B. Therefore, treatment B appeared to be the best fish feed formulation for Red tilapia production.